2020
DOI: 10.3390/genes11070767
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Loci and Pathways Associated with Heifer Conception Rate in U.S. Holsteins

Abstract: Heifer conception rate (HCR) is defined as the percentage of inseminated heifers that become pregnant at each service. The genome-wide association analyses in this study focused on identifying the loci associated with Holstein heifer (n = 2013) conception rate at first service (HCR1) and the number of times bred (TBRD) to achieve a pregnancy. There were 348 unique loci associated (p < 5 × 10−8) with HCR1 and 615 unique loci associated (p < 5 × 10−8) with TBRD. The two phenotypes shared 302 loci, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 84 publications
1
26
0
Order By: Relevance
“…Protein C is a potent anticoagulant and anti-inflammatory molecule which regulates the functions of different epithelial barriers by controlling inflammation [ 30 , 31 ]. Dipeptidyl peptidase-like protein 6 is a transmembrane protein that binds to voltage-gated potassium channels from the Kv4 family [ 32 ], associated with uterine capacity for pregnancy and fertility in beef heifers [ 33 ], and relevant for uterine function [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Protein C is a potent anticoagulant and anti-inflammatory molecule which regulates the functions of different epithelial barriers by controlling inflammation [ 30 , 31 ]. Dipeptidyl peptidase-like protein 6 is a transmembrane protein that binds to voltage-gated potassium channels from the Kv4 family [ 32 ], associated with uterine capacity for pregnancy and fertility in beef heifers [ 33 ], and relevant for uterine function [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Functional genes associated with PY in the EARLY stage of lactation were ATF6 and ELMO1 , while MYOF was associated with PY at the PEAK stage of lactation. Galliou et al [ 43 ] reported that ATF6 is associated with the number of inseminations per conception and first service conception in Holstein dairy cows. This study showed that candidate genes found for PY participate in the regulation of transcription from the RNA polymerase II promoter in response to stress, which can be considered as a mechanism to relieve the stress caused by a negative energy balance in the EARLY stage of lactation.…”
Section: Discussionmentioning
confidence: 99%
“…Infertility or subfertility is a critical barrier to sustainable cattle production [2], including in heifers. For example, approximately 15% [3] and 5% [4] of beef and dairy heifers, respectively, do not calve at 24 months of age. Heifers that calve at an optimum age have greater productivity and longevity in the herd [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Another potential avenue for the identification of infertile heifers is the use of molecular phenotyping [24]. The pioneering efforts focused on genome-wide association studies (GWAS) to identify genetic markers associated with heifer fertility [4,12,[25][26][27][28][29][30][31][32][33][34][35][36][37][38], but only a few seem to be reproducible across populations [37]. More recent efforts have also focused on transcriptome [39][40][41] and metabolome [42] datasets characterizing these molecules in blood samples.…”
Section: Introductionmentioning
confidence: 99%